Childhood Obesity: An Updated Review - Leung, Alexander K.C.; Wong, Alex H.C.; Hon, Kam L. (Current Pediatric Reviews, 2024)
Background: Childhood obesity is an important and serious public health problem worldwide. Objective: This article aims to familiarize physicians with the evaluation, management, and prevention of childhood. Methods: A PubMed search was conducted in May, 2021, in Clinical Queries using the key terms
Keywords: overweight